Early Holocene greening of the Sahara requires Mediterranean winter rainfall - Cheddadi, Rachid (Proc Natl Acad Sci U S A, 2021)
The greening of the Sahara, associated with the African Humid Period (AHP) between ca. 14,500 and 5,000 y ago, is arguably the largest climate-induced environmental change in the Holocene; it is usually explained by the strengthening and northward expansion of the African monsoon in response to orbital forcing. However, the strengthened monsoon in Early to Middle Holocene climate model simulations cannot sustain vegetation in the Sahara or account for the increased humidity in the Mediterranean region. Here, we present an 18,500-y pollen and leaf-wax δD record from Lake Tislit (32° N) in Morocco, which provides quantitative reconstruction of winter and summer precipitation in northern Africa. The record from Lake Tislit shows that the northern Sahara and the Mediterranean region were wetter in the AHP because of increased winter precipitation and were not influenced by the monsoon. The increased seasonal contrast of insolation led to an intensification and southward shift of the Mediterranean winter precipitation system in addition to the intensified summer monsoon. Therefore, a winter rainfall zone must have met and possibly overlapped the monsoonal zone in the Sahara. Using a mechanistic vegetation model in Early Holocene conditions, we show that this seasonal distribution of rainfall is more efficient than the increased monsoon alone in generating a green Sahara vegetation cover, in agreement with observed vegetation. This conceptual framework should be taken into consideration in Earth system paleoclimate simulations used to explore the mechanisms of African climatic and environmental sensitivity.